A PROPOSAL FOR A CLASSIFICATION OF GEOMORPHOLOGICAL SITES DEPENDING ON THEIR TOURIST VALUE - Pralong, Jean-Pierre; Reynard, Emmanuel (Alpine and Mediterranean Quaternary, 2005)
J.P. Pralong & E. Reynard, A proposal for a classification of Geomorphological sites depending on their tourist value. (IT ISSN 0394-3356, 2005). This paper presents theoretical frameworks concerning the relationships between geomorphological landforms and processes and tourist and recreational activities. Firstly, a global model connecting different components of these relationships is proposed. Secondly, a particular model analysing how geomorphological landforms and processes are recognised and assessed as geomorphological sites in a context of tourist optimization and exploitation is developed. Finally, an ensuing classification of geomorphological sites according to the use of their scenic, scientific, cultural and economic values is developed and illustrated by two case studies in the area of Chamonix-Mont-Blanc (Haute-Savoie, France).